Promising practices to connect schools with the community - Hiatt-Michael, Diana B. (Family, school, community, partnership., 2003)
This is the second in a series of monographs by the Family, School, Community Partnership (FSCP) Special Interest Group of the American Educational Research Association. Parent involvement, as one of the eight National Education Goals in 1994, has brought heightened awareness to the importance of connecting educational institutions and their communities. The goal envisions "school partnerships that will increase parent involvement and participation in promoting the social, emotional, and academic growth of children." The U.S. Congress additionally supported this goal in the passage of the No Child Left Behind Act in 2001. This act is the renewal of the Elementary and Secondary Education Act and strongly promotes schools' active involvement with families and the surrounding community.